Da'wah Through Service Excellence: Analyzing Customer Satisfaction in Islamic Aqiqah and Catering Services - Yummil, Yummil; Susanto, Perengki; Patrisia, Dina; Zulvianti, Nora; Audila, Fitri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This research examines the impact of product and service quality on customer satisfaction within the context of Islamic aqiqah and catering services, integrating a da'wah (Islamic outreach) perspective. Aqiqah services hold significant religious importance in Islamic culture, serving not only as commercial enterprises but also as vehicles for preserving and promoting Islamic traditions. Customers often encounter challenges regarding product and service quality in the marketing process, which directly affects their satisfaction levels. This study employs a quantitative research method with data analysis conducted using SPSS software. Primary data were collected from 72 customers using simple random sampling from a population of 264 customers who have utilized aqiqah and catering services, while secondary data were obtained from service provider documents. The findings reveal that product and service quality collectively explain 24.5% of customer satisfaction variance (R² = 0.245), with the remaining 75.5% attributed to other variables not examined in this study. Specifically, the t-test results indicate that service quality significantly influences customer satisfaction (t = 4.604, p < 0.05), while product quality does not show significant impact (t = 0.082, p = 0.935). The F-test confirms that both variables together significantly affect customer satisfaction (F = 11.366, p < 0.05). These results suggest that customers prioritize service excellence over product attributes when evaluating religious-based services, indicating that da'wah through exceptional service delivery can enhance both commercial success and religious mission fulfillment in Islamic business enterprises.